Gemcitabine-Resistant Biomarkers in Bladder Cancer are Associated with Tumor-Immune Microenvironment - Song, Yuxuan; Du, Yiqing; Qin, Caipeng; Liang, Haohong; Yang, Wenbo; Lin, Jiaxing; Ding, Mengting; Han, Jingli; Xu, Tao (Frontiers in Cell and Developmental Biology, 2022)
To identify key biomarkers in gemcitabine(GEM)-resistant bladder cancer (BCa) and investigate their associations with tumor-infiltrating immune cells in tumor immune microenvironment, we performed the present study on the basis of large-scale sequencing data. Expression profiles from Gene Expression Omnibus GSE77883 dataset and The Cancer Genome Atlas BLCA dataset were analyzed. Both BCa development and GEM-resistance were identified to be immune-related through evaluating tumor-infiltrating immune cells. Eighty-two DEGs were obtained to be related to GEM-resistance. Functional enrichment analysis demonstrated they were related to regulation of immune cells proliferation. Protein-protein interaction network selected 6 key genes (CAV1, COL6A2, FABP4, FBLN1, PCOLCE and CSPG4). Immunohistochemistry confirmed the down-regulation of the 6 key genes in BCa. Survival analyses revealed the 6 key genes were significantly associated with BCa overall survival. Correlation analyses revealed the 6 key genes had high infiltration of most immune cells. Gene set enrichment analysis further detected the key genes might regulate GEM-resistance through immune response and drug metabolism of cytochrome P450. Next, microRNA-gene regulatory network identified 3 key microRNAs (hsa-miR-124-3p, hsa-miR-26b-5p and hsa-miR-192-5p) involved in GEM-resistant BCa. Connectivity Map analysis identified histone deacetylase inhibitors might circumvent GEM-resistance. In conclusion, CAV1, COL6A2, FABP4, FBLN1, PCOLCE and CSPG4 were identified to be critical biomarkers through regulating the immune cells infiltration in immune microenvironment of GEM-resistance and could act as promising treatment targets for GEM-resistant muscle-invasive BCa.